2010
DOI: 10.1002/maco.200905439
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural investigation of the oxide formed on TP 347H FG during long‐term steam oxidation

Abstract: The long-term oxidation behaviour of TP347H FG in ultra supercritical steam conditions was assessed by exposing the steel in test superheater loops in a Danish coal-fired power plant and characterising the oxide layer with reflective light and electron microscopy. Double layered oxide scales formed during steam oxidation. TEM investigations reveal that the inner oxide layer consists of particles of metallic Ni/Fe and Fe-Cr spinel in the interior of the former alloy grains and a compact layer of Fe-Cr spinel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 25 publications
5
20
0
Order By: Relevance
“…At 700 C in steam, internal attack of grain boundaries was observed for up to several microns into the alloy after 100 hours and up to approximately ten microns after 250 hours. Similar effects have been reported in other studies, such as by Wild [26], who reported the grain boundary oxide to be rich in Si at 797 C. Hansson et al [17], observed Cr-rich grain boundary attack when oxidising TP347HFG at 595 C in 25.6 MPa steam. The observed grain boundary attack may have resulted from the existence of a less protective Mn -Cr spinel compared with Cr 2 O 3 at the spinelyalloy interface allowing oxygen to penetrate the underlying alloy grain boundaries.…”
Section: Oxide Morphologysupporting
confidence: 86%
See 1 more Smart Citation
“…At 700 C in steam, internal attack of grain boundaries was observed for up to several microns into the alloy after 100 hours and up to approximately ten microns after 250 hours. Similar effects have been reported in other studies, such as by Wild [26], who reported the grain boundary oxide to be rich in Si at 797 C. Hansson et al [17], observed Cr-rich grain boundary attack when oxidising TP347HFG at 595 C in 25.6 MPa steam. The observed grain boundary attack may have resulted from the existence of a less protective Mn -Cr spinel compared with Cr 2 O 3 at the spinelyalloy interface allowing oxygen to penetrate the underlying alloy grain boundaries.…”
Section: Oxide Morphologysupporting
confidence: 86%
“…In these cases, particles of Cr-rich oxide existed in a spinel containing concentrations of Fe, Ni, Cr, Mn and Cu. Separate studies by Hansson et al [17,24] and Jianmin et al [25] have reported similar morphologies and provided models for growth on TP347HFG in steam at 25.6 MPa. At 600 C, there was a high number of partially oxidised grains with an approximately uniform distribution of oxidised alloying elements.…”
Section: Oxide Morphologymentioning
confidence: 84%
“…Effects of H2O vapour on high temperature corrosion of materials have been widely investigated in the absence of deposits (relevant to steamside oxidation of superheater tubes) [28][29][30][31][32][33][34][35][36][37][38]. Generally the corrosion results in an outward growing magnetite layer and an inward growing Fe-Cr spinel phase.…”
mentioning
confidence: 99%
“…Also the resistance against steam oxidation has turned out to be satisfactory. 31 Steels have also been run in test loops at higher steam conditions. Probably the most well-known tests are those for six austenitic steels in the Eddystone Power Station.…”
Section: Application Of the Steelsmentioning
confidence: 99%